Blood culture patterns and antibiotic resistance in preterm low birth weight babies with neonatal sepsis - Jahan, Ishrat; Barkat, Shahreen; Sharmeen, Rumana; Huq, Nadia; Kundu, Sanjib (International Journal of Contemporary Pediatrics, 2026)
Background: Neonatal sepsis remains a leading cause of morbidity and mortality among preterm infants and rising antimicrobial resistance (AMR) among Gram-negative pathogens poses a significant challenge to treatment. This study evaluated blood culture patterns, antibiotic resistance and clinical outcomes in neonates with sepsis admitted to a tertiary care center in Bangladesh. Methods: A retrospective observational study was conducted in the NICU of Bangladeshi Specialized Hospital, Dhaka, from January 2023 to December 2024. A total of 144 neonates (0–28 days) with suspected or confirmed bacterial sepsis were analyzed. Demographic, clinical, laboratory and treatment data were extracted and blood culture isolates were tested for antibiotic susceptibility using the VITEK 2 system per CLSI guidelines. Results: The majority of neonates were male (59.7%) and early preterm (50%), with a mean admission age of 2.92±2.21 days. Late-onset sepsis predominated (73.61%) and respiratory distress was the most common clinical sign (66.67%). Blood culture positivity was 22.92%, with Klebsiella pneumoniae (51.52%) and Acinetobacter spp. (33.33%) being the most common isolates. Klebsiella pneumoniae was 100% sensitive to tigecycline and 94.1% to colistin but showed <6% sensitivity to first-line antibiotics. Supportive care included phototherapy (75%), NG feeding (70.14%) and CPAP (63.89%). Survival at discharge was 96.53%, with a mean NICU stay of 14.82±8.24 days. Conclusions: MDR Gram-negative sepsis is a growing threat in NICUs, with declining efficacy of first-line antibiotics. The reliance on colistin and tigecycline raises concerns for future treatment options if resistance to these agents develops. Strong infection control, antimicrobial stewardship and updated antibiogram surveillance are essential to combat this trend.